Odpowiedź :
Odpowiedź:
a)
a1=1
an= a1+ (n-1) *r
r=1
1000=1+(n-1)*1
1000=1+n-1
1000-1+1=n
1000=n
S1000=[(1+1000)/2]*1000
S1000= 1001/2*1000
S1000= 500,5*1000=500500
b)
a1=7
an=7+(n-1)*0,5
r=0,5
an=7+0,5n-0,5
192,5=7+0,5n-0,5
192,5+0,5-7=0,5n
186=0,5n/:(0,5)
n=372
S372=[(7+192,5)/2]*372
S372=[199,5/2)*372=99,75*373=37107
Odpowiedź:
Szczegółowe wyjaśnienie:
a) Sn={(a1+an2)/2}⋅n i an=a1+(n−1)⋅r
S= {(1+1000)/2}*n, gdzie n=1000
(bo 1000=1+(n-1)*1)
S= (1001/2)*1000= 500500
b) S={(7+192,5)/2}*n, gdzie n=372
(bo 192,5= 7+(n-1)*0,5)
186=1/2n
n=372
S={(7+192,5)/2}*372= 37107